A Study on Machine Learning and Python’s Framework - Chandel, Meghna; Silakari, Sanjay; Rajeev Pandey; Sharma, Smita (International Journal of Computer Sciences and Engineering, 2022)
The present paper is based on Machine Learning Activities using Python programming language. There are various types of Machine Learning Algorithms such as Supervised Learning, Unsupervised Learning and Reinforcement Learning. These already exist in the field of computer programming. Besides these algorithms there is another Deep Learning algorithm which plays a significant role in machine learning devices and is part of Machine Learning methods. The Deep Learning can be used to intelligently analyze the data on a large scale. The paper explores that how Python can be applied in the ML methods? A comprehensive overview on the concerned issues has been illustrated in the study. The present research paper explores the history of machine learning, the methods used in machine learning, its application in different fields of AI. The aim of this study is to transmit the knowledge of machine learning in various fields of AI. In Machine Learning (ML) the knowledge of Artificial Intelligence (AI) is very much essential.